2006
DOI: 10.1177/1557085106292778
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Juvenile Justice Decision Making

Abstract: This study examines the independent and interactive effects of race and gender on juvenile justice decision making. Using data from a sample of juvenile court referrals from two midwestern juvenile courts, this study looks at males and females separately by race. The results indicate that the effect of race on the pre-adjudication detention and disposition outcomes varies by gender. The severity or leniency of the outcomes is determined by race, gender, and an interaction of the two. This study underscores the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(120 citation statements)
references
References 66 publications
(92 reference statements)
7
110
0
3
Order By: Relevance
“…In some research, the influence of extralegal factors dissolves after legal factors are controlled (Belknap, 2001;Carter, 1979;Clarke & Koch, 1980;Dannefer & Schutt, 1982;Fenwick, 1982;Kempf-Leonard & Sontheimer, 1995;Phillips & Dinitz, 1982;Teilmann & Landry, 1981). However, other research has revealed that extralegal factors continue to influence juvenile court outcomes even when legal factors are included (Bishop, 2005;Bishop & Frazier, 1996;Bray, Sample, & Kempf-Leonard, 2005;Conley, 1994;Frazier & Bishop, 1995;Guevara, Herz, & Spohn, 2006;Guevara, Spohn, & Herz, 2004;Leiber, 1994;Thornberry & Christensen, 1984;Wordes & Bynum, 1995;Wordes et al, 1994). Pope and Feyerherm's (1990) review of 46 studies on juvenile court outcomes emphasized the need to take extralegal factors such as race into consideration.…”
Section: Research On Racial Disparities In Juvenile Court Outcomesmentioning
confidence: 94%
“…In some research, the influence of extralegal factors dissolves after legal factors are controlled (Belknap, 2001;Carter, 1979;Clarke & Koch, 1980;Dannefer & Schutt, 1982;Fenwick, 1982;Kempf-Leonard & Sontheimer, 1995;Phillips & Dinitz, 1982;Teilmann & Landry, 1981). However, other research has revealed that extralegal factors continue to influence juvenile court outcomes even when legal factors are included (Bishop, 2005;Bishop & Frazier, 1996;Bray, Sample, & Kempf-Leonard, 2005;Conley, 1994;Frazier & Bishop, 1995;Guevara, Herz, & Spohn, 2006;Guevara, Spohn, & Herz, 2004;Leiber, 1994;Thornberry & Christensen, 1984;Wordes & Bynum, 1995;Wordes et al, 1994). Pope and Feyerherm's (1990) review of 46 studies on juvenile court outcomes emphasized the need to take extralegal factors such as race into consideration.…”
Section: Research On Racial Disparities In Juvenile Court Outcomesmentioning
confidence: 94%
“…More recently, a variety of researchers have called for this type of approach; Burgess-Proctor, 2006, Carr & Alfieri, 2006Guevara et al, 2006).…”
Section: The Intersectionality Perspectivementioning
confidence: 98%
“…Bien que ce résultat soit nouveau puisqu'il se rapporte spécifiquement aux jeunes délinquants victimes de maltraitance, il est plutôt conforme aux conclusions de Ryan et al (2007), qui énoncent que les jeunes délin-quants de sexe masculin étaient plus à risque de recevoir des peines d'emprisonnement que les jeunes délinquantes. Ces conclusions correspondent également à d'autres recherches montrant que les jeunes adolescentes à comportements délinquants reçoivent des peines moins sévères que leurs pairs masculins, même lorsque des variables telles que les antécédents et la gravité de l'infraction sont prises en compte (Bishop et Frazier, 1992 ;Farrington et Morris, 1993 ;Guevara, Herz et Spohn, 2006 ;Johnson et Shueble, 1991 ;Steffensmeier et al, 1998). Nos conclusions rejoignent aussi la théorie des préoccupations sociales appliquée à la détermination des peines et sa conception de la dangerosité du contrevenant.…”
Section: Discussionunclassified
“…Nos conclusions rejoignent aussi la théorie des préoccupations sociales appliquée à la détermination des peines et sa conception de la dangerosité du contrevenant. Puisque les garçons sont perçus comme plus dangereux, plus menaçants, et plus à risque de récidive que les jeunes filles, ils sont sujets à des peines plus sévères que ces dernières (Guevara et al, 2006).…”
Section: Discussionunclassified
See 1 more Smart Citation